2019
DOI: 10.3390/w11102130
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Impacts of Climate Change and Downscaling Methods on Future Runoff Projections in the Biliu River Basin

Abstract: This paper assesses the uncertainties in the projected future runoff resulting from climate change and downscaling methods in the Biliu River basin (Liaoning province, Northeast China). One widely used hydrological model SWAT, 11 Global Climate Models (GCMs), two statistical downscaling methods, four dynamical downscaling datasets, and two Representative Concentration Pathways (RCP4.5 and RCP8.5) are applied to construct 22 scenarios to project runoff. Hydrology variables in historical and future periods are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Historical and future simulated data on the predictors required for the SDSM were derived from the second-generation Canadian Earth System Model (CanESM2) developed by the Canadian center for climate modeling and analysis (CCCma) (von Salzen et al 2013;Khadka and Pathak 2016;Huang et al 2016;Zhu et al 2019). The model is a part of the fifth Coupled Model Inter Comparison Project (CMIP5) and is currently the only CMIP5 model for which readyto-use SDSM predictors are available.…”
Section: Gcm/ncep Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Historical and future simulated data on the predictors required for the SDSM were derived from the second-generation Canadian Earth System Model (CanESM2) developed by the Canadian center for climate modeling and analysis (CCCma) (von Salzen et al 2013;Khadka and Pathak 2016;Huang et al 2016;Zhu et al 2019). The model is a part of the fifth Coupled Model Inter Comparison Project (CMIP5) and is currently the only CMIP5 model for which readyto-use SDSM predictors are available.…”
Section: Gcm/ncep Datamentioning
confidence: 99%
“…Statistical downscaling on the other hand relies upon the empirical relationships between the observed data and the large-scale predictors and has the advantages of being simple in application and also computationally less demanding (Samadi et al 2013). Among the different Statistical downscaling approaches, Statistical Downscaling Model (SDSM) is a popular method used globally for climate change assessment and impact studies (Wilby et al 2002;Gagnon et al 2005;Chu et al 2010;Huang et al 2011;Mahmood and Babel 2014;Zhu et al 2019). Numerous comparative studies have pointed out the ability of SDSM to perform better than other downscaling techniques in simulating the current and future climate variability with confidence (Coulibaly et al 2005;Khan et al 2006;Chen et al2011;Teutschbein et al2011;Samadi et al2013).…”
Section: Introductionmentioning
confidence: 99%
“…R e values are −5.38% in the validation period. More details about the calibration and validation were introduced in Zhu et al [54].…”
Section: Hydrological Model Parameters Calibrated and Uncertaintymentioning
confidence: 99%
“…In contrast with the global climate modelling, the downscaling and bias-correction steps used in the driving climate data did not use alternative models or methods. The choice of downscaling can have an impact on hydrological projections [65], particularly if the method does not account for orographic effects [66], and the use of just a single climate model in the dynamic downscaling here is a particular weakness of the climate projections [23,67]. Similarly, the global study by Iizumi, et al [68], comparing two bias-correction methods, showed that while the choice of methods contributed little to the uncertainties in temperature projections, the choice of methods was a major contributor to precipitation uncertainties.…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%